Therapeutic plasma exchange performed in tandem with hemodialysis without supplemental calcium in the apheresis circuit. Issue 3 (13th May 2016) - Zhao, Yong; Ibrahim, Hiba; Bailey, Jeffrey A.; Linden, Jeanne; Hickson, Elda; Haynes, Stefanie; Greene, Mindy; Vauthrin, Michelle; Weinstein, Robert
Abstract : Therapeutic plasma exchange (TPE) and hemopoietic progenitor cell (HPC) collection are apheresis procedures that can safely be performed in tandem with hemodialysis. Despite the return of citrate‐anticoagulated blood to the patient during HPC collection, it is not necessary to administer supplemental calcium during these procedures because the ionized calcium concentration is restored as the returning blood passes through the dialyzer. It is not known whether this applies to TPE, in which a mixture of blood and pharmaceutical albumin, an avid binder of plasma ionized calcium, is returned to the patient through the dialyzer. We report on three dialysis‐dependent patients who required TPE and underwent tandem treatments without supplemental calcium in the apheresis circuit. Overall, ionized calcium fell 4–12% ( P  = 0.0.024) and patients reported no symptoms of hypocalcemic toxicity. Tandem hemodialysis/TPE can be performed without supplemental calcium in the apheresis circuit. J. Clin. Apheresis 32:154–157, 2017. © 2016 Wiley Periodicals, Inc.